2018
DOI: 10.1021/acsnano.7b07402
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Gold Nanorods: Purcell Effect Enhanced Emission from Hot Carriers

Abstract: We demonstrate, experimentally and theoretically, that the photon emission from gold nanorods can be viewed as a Purcell effect enhanced radiative recombination of hot carriers. By correlating the single-particle photoluminescence spectra and quantum yields of gold nanorods measured for five different excitation wavelengths and varied excitation powers, we illustrate the effects of hot carrier distributions evolving through interband and intraband transitions and the photonic density of states on the nanorod p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
194
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(215 citation statements)
references
References 68 publications
(142 reference statements)
21
194
0
Order By: Relevance
“…The synthesis of gold nanorods (AuNRs) is of considerable interest owing to their unique optical properties, which can be used for imaging, surface‐enhanced Raman spectroscopy (SERS), diagnostics, sensing, and biological applications . Murphy et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of gold nanorods (AuNRs) is of considerable interest owing to their unique optical properties, which can be used for imaging, surface‐enhanced Raman spectroscopy (SERS), diagnostics, sensing, and biological applications . Murphy et al .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of gold nanorods (AuNRs)i so fc onsiderable interest owing to their unique optical properties,w hich can be used for imaging, [1][2][3][4][5][6][7][8] surface-enhanced Raman spectroscopy (SERS), [9][10][11][12] diagnostics, [13][14][15] sensing, [16,17] and biologicala pplications. [18][19][20][21][22][23][24] Murphy et al [25] first reported the seed-mediated chemicals ynthesis of AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmons enhance photoluminescence in metal nanomaterials [27]. To apply this concept for 2D semiconductors and acquire all light spectral features of H-SiB monolayers including thermal parameters on the light emission, we further compute the polarizability matrix.…”
Section: Light Emissionmentioning
confidence: 99%
“…Several experiments can probe this dynamic path directly in metals through time-resolved ultrafast pump probe [24] or indirectly by scanning changes of SP resonances [25]. For following of electro-optic and vibrational modes in molecules, fluorescence is a powerful tool [26], while light emission in metals is weaker than molecules due to strong electron-electron (e-e) interaction and electron-phonon (e-ph) coupling [27]. Barati et al [28] reported efficient electron-hole (e-h) pair generation in the transition-metal dichalcogenides (TMDs) semiconductors at temperatures near T = 300 K, resulting in 350% enhancement in the optoelectronic responsively [28].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This tunability of GNRs can be further enriched by collective plasmon coupling through the formation of periodic arrays of GNRs, [6,7] and thus provides potential applications such as sensors, [8][9][10][11][12][13] broadband absorbers, [14] plasmonic catalysts, [15] and other plasmonic devices. [1][2][3][4][5] This tunability of GNRs can be further enriched by collective plasmon coupling through the formation of periodic arrays of GNRs, [6,7] and thus provides potential applications such as sensors, [8][9][10][11][12][13] broadband absorbers, [14] plasmonic catalysts, [15] and other plasmonic devices.…”
Section: Introductionmentioning
confidence: 99%